Usability of an Adaptive Computer Assistant that Improves Self-care and Health Literacy of Older Adults - Blanson Henkemans, O. A. (2008)
OBJECTIVES: We developed an adaptive computer assistant for the supervision of diabetics’ self-care, to support limiting illness and need for acute treatment, and improve health literacy. This assistant monitors self-care activities logged in the patient’s electronic diary. Accordingly, it provides context-aware feedback. The objective was to evaluate whether older adults in general can make use of the computer assistant and to compare an adaptive computer assistant with a fixed one, concerning its usability and contribution to health literacy. METHODS: We conducted a laboratory experiment in the Georgia Tech Aware Home wherein 28 older adults participated in a usability evaluation of the computer assistant, while engaged in scenarios reflecting normal and health-critical situations. We evaluated the assistant on effectiveness, efficiency, satisfaction, and educational value. Finally, we studied the moderating effects of the subjects’ personal characteristics. RESULTS: Logging self-care tasks and receiving feedback from the computer assistant enhanced the subjects’ knowledge of diabetes. The adaptive assistant was more effective in dealing with normal and health-critical situations, and, generally, it led to more time efficiency. Subjects’ personal characteristics had substantial effects on the effectiveness and efficiency of the two computer assistants. CONCLUSIONS: Older adults were able to use the adaptive computer assistant. In addition, it had a positive effect on the development of health literacy. The assistant has the potential to support older diabetics’ self care while maintaining quality of life.